Sleep Increases Susceptibility to the Misinformation Effect. Issue 6 (19th July 2016) - Calvillo, Dustin P.; Parong, Jocelyn A.; Peralta, Briana; Ocampo, Derrick; Van Gundy, Rachael
Summary: When individuals witness an event and are exposed to misleading postevent information, they often incorporate the misleading information into their memory for the original event, a phenomenon known as the misinformation effect. The present study examined the role of sleep in the misinformation effect. Participants (N = 177) witnessed two events; were exposed to misleading postevent information immediately, 12 hours later the same day, 12 hours later the next day, or 24 hours later; and then took a recognition test. All groups demonstrated the misinformation effect, and this effect was larger in groups with an overnight retention interval. Signal detection analyses revealed that sleep decreased sensitivity. These results suggest that sleep increases susceptibility to the misinformation effect, which may occur because sleep results in gist‐based representations of original events or because sleep improves learning of postevent information. Implications for interviewing eyewitnesses are discussed. Copyright © 2016 John Wiley & Sons, Ltd.